THE DEVELOPMENT OF THE STUDENT INTELLIGENCE IN PERIOD OF BASIC EDUCATION IN MOESLIM FAMILY ENVIRONMENT (MENGEMBANGKAN KECERDASAN PESERTA DIDIK PADA PERIODE PENDIDIKAN DASAR DI LINGKUNGAN KELUARGA MUSLIM) - Nurjanah Nurjanah (al-Afkar, Journal For Islamic Studies, 2019)
This article aims to explore: 1) the concept of intelligence according to the perspective of Islamic education, 2) the intelligence development of students in the basic education period, and 3) the methods for developing intelligence of students in the period of basic education in Muslim families The basic concept of intelligence in a long-developed Islamic education perspective is: a) intellectual intelligence (thinking intelligence), b) emotional intelligence (moral), c) spiritual intelligence (spiritual intelligence). Efforts to develop students' intelligence in the basic education period can be done by applying methods: a) educating through the dialogue of the Qur'an and Nabawi, b) educating through the stories of the Qur'an and Nabawi, c) educating through parables, d) educating through exemplary, e) educating through 'Ibrah and willing, and f) educating through targibs and tarhib. Efforts to develop the intelligence of students in the period of basic education in the Muslim family environment must be based on Al_qur'an and As-Sunnah with the following description: 1) listening to the recitation of the Qur'an, 2) giving advice with good stories from Al -Qur'an and As-Sunnah, 3) Educating with parables derived from the Qur'an, 4) Educating by giving good moral example so that students can develop emotional intelligence, 5) Educating through 'ibrah and want' izah. Education can prepare learning designs that can stimulate students' thinking and thinking. Give pleasant hopes (Targhib) and punishment (Tarhib) Tujuan penulisan artikel ini untuk: 1) mengetahui konsep kecerdasan menurut perspektif pendidikan Islam, 2) mengetahui perkembangan kecerdasan peserta didik pada periode pendidikan dasar, dan 3) umengetahui metode pengembangan kecerdasan peserta didik pada periode pendidikan dasar di lingkungan keluarga muslim. Konsep dasar kecerdasan dalam perspektif pendidikan Islam yang sudah berkembang lama adalah: a) kecerdasan intelektual (kecerdasan berpikir), b) kecerdasan emosional (akhlak), c) kecerdasan spiritual (kecerdasan ruhaniah). Upaya mengembangkan kecerdasan peserta didik pada periode pendidikan dasar dapat dilakukan dengan menerapkan metode: a) mendidik melalui dialog Al-Qur’an dan Nabawi, b) mendidik melalui kisah Al-Qur’an dan Nabawi, c) mendidik melalui perumpamaan, d) mendidik melalui keteladanan, e) mendidik melalui ‘Ibrah dan mau’izah, dan f) mendidik malalui targib dan tarhib. Upaya mengembangkan kecerdasan peserta didik pada periode pendidikan dasar di lingkungan keluarga muslim harus didasarkan pada Al Qur’an dan As-sunnah dengan uraian sebagai berikut: 1) mendengarkan tilawah Al-Qur’an, 2) memberikan nasehat dengan kisah-kisah yang baik dari Al-Qur’an dan As-Sunnah, 3) mendidik dengan perumpamaan yang bersumber dari Al-Qur’an, 4) mendidik dengan memberikan keteladanan dalam akhlak yang baik sehingga dapat mengembangkan kecerdasan emosional peserta didik, 5) mendidik melalui ‘ibrah dan mau’izah. Pendidikan dapat menyiapkan rancangan pembelajaran yang dapat merangsang perenungan dan berpikirnya peserta didik. Memberikan harapan yang menyenangkan (Targhib) dan hukuman (Tarhib).